Justice sensitivity of youth with different levels of income as an actual socio-psychological problem - A. S. Dementiev; N. A. Tsvetkova (Вестник университета)
The article substantiates the relevance of studying the socio-psychological determinants of sensitivity to justice in Russian youth with different levels of wealth. The sensitivity to justice concept itself has been revealed, its structure presented and its evolution shown; the wealth concept has been given. Four roles that a person can occupy in situations subjectively perceived as unfair (a ‘victim’ – the injustice is committed towards them; a ‘witness’ – they observe injustice towards another people; a ‘beneﬁciary’ – a person beneﬁts from the situation of injustice towards another one; a ‘violator’ – they act unfairly) have been characterized. A review of domestic and foreign studies of the relationship among sensitivity to justice and other personality characteristics, carried out over the past ﬁve years on various samples, has been given. Prospects for research into various aspects of this scientiﬁc problem, including cross-cultural differences, have been shown. Sensitivity to justice in modern social psychology is characterized as a relatively independent personality trait, but its socio-psychological determination is poorly studied. The model of empirical research of socio-psychological determinants of sensitivity to justice in youth with different levels of wealth has been presented.